Coping strategy and substance use disorders: The mediating role of drug hazard knowledge - Ismail, Wahyuni; Damayanti, Eka; Nurpahmi, Sitti; Hamid, Dayang Hjh Tiawa Awg Hj (Faculty of Psychology and Health - Universitas Islam Negeri Walisongo Semarang, 2021)
Substance Use Disorder (SUD) is a social phenomenon that has plagued communities, including adolescents. Coping strategy and drug hazard knowledge are seen as important factors in curbing drug use amongst young people. This study aims to identify the indirect influence of coping strategy through drug hazard knowledge as a mediator in substance use disorders. The research employed a quantitative approach with a cross-sectional design, with a sample of 381 adolescents, 313 males and 68 females, selected using a simple random sampling technique. The research instruments comprised the Drugs Abuse Screening Test-28, a coping scale, and drug hazard knowledge scale. AMOS 20.0 for Structural Equation Modelling (SEM) was used for the analysis. The results show no significant indirect influence of coping strategy through drug hazard knowledge as a mediator in substance use disorder among adolescents. This indicates that drug hazard knowledge has no significant influence on substance use disorders.